Studi Komparasi Strategi The Power Of Two Dengan Strategi Index Card Match Terhadap Hasil Belajar Ipa Siswa Kelas Iii Mim Pk Kartasura Tahun Ajaran 2015/2016 - Fajarwati, Sarilia; , Dra. Sri Hartini, S.H., M.Pd (2016)
This study aims to determine: 1) The different effect in the use of learning strategies The Power Of Two and Index Card Match the learning outcomes of the third grade science students MIM PK Kartasura the academic year 2015/2016. 2) To know better learning strategy between strategy The Power Of Two strategies Index Card Match the learning outcomes of the third grade science students MIM PK Kartasura the academic year 2015/2016. This research is a quantitative experiment. The analysis technique used in this study using t-test. Based on data analysis with a significance level of 5% obtained t> t table (2.982> 1.997) with the average value of the first experimental class is greater than the average value of the experimental class II, namely 73.79> 71.36. It can be concluded that: There is a difference of influence in the use of learning strategies The Power Of Two and learning strategies Index Card Match the learning outcomes of the third grade science students MIM PK Kartasura the academic year 2015/2016. Based on t test result that t count> t table namely 2.982> 1.997 (accepted). Learning Strategies The Power Of Two is better than learning strategy Index Card Match the learning outcomes of the third grade science students MIM PK Kartasura the academic year 2015/2016. Based on the average of the experimental class I is greater than the average of the experimental class II, namely 73.79> 71.36 (rejected) because the previous hypotheses predicted that learning strategies Index Card Match will have a higher learning outcomes than the learning outcomes' strategy the Power Of Two. Keywords: Learning Outcomes, Strategies The Power Of Two, Strategy Index Card Match